Topography-Mediated Enhancement of Nonviral Gene Delivery in Stem Cells - Lu Ge; Liangliang Yang; Reinier Bron; Patrick van Rijn (MDPI AG, 2022)
Gene delivery holds great promise for bioengineering, biomedical applications, biosensors, diagnoses, and gene therapy. In particular, the influence of topography on gene delivery is considered to be an attractive approach due to low toxicity and localized delivery properties. Even though many gene vectors and transfection systems have been developed to enhance transfection potential and combining it with other forms of stimulations could even further enhance it. Topography is an interesting surface property that has been shown to stimulate differentiation, migration, cell morphology, and cell mechanics. Therefore, it is envisioned that topography might also be able to stimulate transfection. In this study, we tested the hypothesis "topography is able to regulate transfection efficiency", for which we used nano- and microwave-like topographical substrates with wavelengths ranging from 500 nm to 25 µm and assessed the transfectability of human bone marrow-derived mesenchymal stem cells (hBM-MSCs) and myoblasts. For transfection, Lipofectamine 2000 and a gene encoding plasmid for red-fluorescent protein (m-Cherry) were used and topography-induced cell morphology and transfection efficiency was analyzed. As a result, topography directs cell spreading, elongation, and proliferation as well as the transfection efficiency, which were investigated but were found not to be correlated and dependent on the cell type. A 55% percent improvement of transfection efficiency was identified for hBM-MSCs grown on 2 µm wrinkles (24.3%) as compared to hBM-MSCs cultured on flat controls (15.7%). For myoblast cells, the highest gene-expression efficiency (46.1%) was observed on the 10 µm topography, which enhanced the transfection efficiency by 64% as compared to the flat control (28.1%). From a qualitative assessment, it was observed that the uptake capacity of cationic complexes of TAMRA-labeled oligodeoxynucleotides (ODNs) was not topography-dependent but that the intracellular release was faster, as indicated by the positively stained nuclei on 2 μm for hBM-MSCs and 10 μm for myoblasts. The presented results indicate that topography enhances the gene-delivery capacity and that the responses are dependent on cell type. This study demonstrates the important role of topography on cell stimulation for gene delivery as well as understanding the uptake capacity of lipoplexes and may be useful for developing advanced nonviral gene delivery strategies.